Feasibility of self-pre-stressing concrete members using shape memory alloys. (December 2015) - Ozbulut, Osman E; Hamilton, Reginald F; Sherif, Muhammad M; Lanba, Asheesh
Shape memory alloys are a class of smart materials that recover apparent plastic deformation (∼6%–8% strain) after heating, thus "remembering" the original shape. This shape memory effect can be exploited for self-post-tensioning applications, and NiTi-based shape memory alloys are promising as shape memory effect is possible at elevated temperatures amenable to practical application compared to conventional NiTi. This study investigates the feasibility of self-post-tensioned concrete elements by activating the shape memory effect of NiTiNb, a class of wide-hysteresis shape memory alloys, using the heat of hydration of grout. First, the microstructure characterization of the NiTiNb wide-hysteresis shape memory alloys is discussed. Then, the tensile stress-induced martensitic transformations in NiTiNb shape memory alloy tendons are studied. Next, the temperature increase due to the heat of hydration of four commercially available grouts is investigated. Pull-out tests are also conducted to investigate the bond between the grout and shape memory alloy bar. Results show that the increase in temperature due to hydration heat can provide significant strain recovery during a free recovery experiment, while the same temperature increase only partially activates the shape memory alloys during a constrained recovery.